Evaluating place-based job creation programs in Japan - Sachiko Kazekami (IZA Journal of Labor Policy, 2017)
First, this paper empirically evaluates the incidence of the Japanese place-based job creation program, which has rarely been studied in Japan. The program increases employment, especially in the agricultural, retail trade, and service sectors, which most treated municipalities promote. Second, this paper explores the municipalities that the program affects most. Those with large aging populations and those with small working age populations decrease the effects of the program. Third, this paper assesses the externality effect of this program and does not observe a strong reduction in sales, workers, or establishments in the neighboring municipalities of a treated municipality.
Keywords: J23; J68; R23; H22; H23; 330; Place-based policy; Job creation; Unemployment; Externality effect